2023
DOI: 10.1155/2023/4845887
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Ovarian Serous Borderline Tumor with Non-Invasive Endometrial Implants

Abstract: Herein, we are presenting a case of a 33-year-old woman who presented to the emergency department complaining of persistent lower abdominal pain of one-day duration. Physical examination revealed abdominal tenderness with right lower quadrant rebound tenderness. Computed tomography abdomen/pelvis showed a 6 cm possible necrotic mass of the left ovary with moderate amount of complex ascites. A laparoscopic left oophorectomy with bilateral salpingectomy, right ovarian biopsy, and appendectomy were performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Extra-ovarian involvement is usually seen in the omentum, peritoneal surface of organs, and abdominal wall (6). Rare organ involvements such as the brain and endometrial involvement has been reported in rare cases in the literature (7,8). Endometrial implant was not observed in our case.…”
Section: Discussionmentioning
confidence: 42%
“…Extra-ovarian involvement is usually seen in the omentum, peritoneal surface of organs, and abdominal wall (6). Rare organ involvements such as the brain and endometrial involvement has been reported in rare cases in the literature (7,8). Endometrial implant was not observed in our case.…”
Section: Discussionmentioning
confidence: 42%